Upaya Pendidikan Masyarakat Lalu Lintas oleh Unit Dikyasa dalam Menekan Angka Kecelakaan Di Wilayah Hukum Polres Ciamis - Alhafizh, Dicky Fariz Rahmad (Indonesian Journal of Police Studies, 2020)
ABSTRACT This research is motivated by traffic accidents that occur in the Legal Area of ​​Ciamis Police Station which have relatively increased, based on the findings of accidents that occurred in 2016 were 309 cases, in 2017 there were 322 traffic accidents, then in 2018 there was an increase drastic of 375 cases of accidents, but in 2019 it decreased to 334 cases, but not yet up to the previous year's figures. The purpose of this study is to describe the efforts made by the Dikyasa Unit to reduce the number of traffic accidents, the factors that cause traffic accidents and the inhibiting factors of the Dikyasa Unit in suppressing the number of traffic accidents in the Ciamis District Police jurisdiction. Theories and concepts used are Management theory (George R. Terry), Communication Theory (Harold Lasswell), Efforts Concepts, Concept of Traffic Control, Road Traffic Concepts and the concept of traffic accidents. The study was conducted with a qualitative approach and method and field research approach as well as data collection techniques accompanied by interviews, observations and documentary studies. Traffic accidents in general have increased from 2016 to 2019. Traffic accidents are caused by human, vehicle, road and environmental factors. Communication as the key to the implementation of Dikmaslantas consisting of whom, what to say, through what channels, to whom and with what effect has not gone well. Not well implemented management functions consisting of planning, organizing, implementing and controlling plus 6 elements of management to achieve goals consisting of humans, materials, methods, machines, money and markets. Dikyasa Unit, especially to the Ciamis Regional Police Chief to increase the number of Dikyasa unit members, as well as to improve the ability of personnel with Dikjur and Education related to the activities of the Traffic Control, to complete the facilities and infrastructure of the Dikyasa unit, to utilize technology, especially social media, in the activities of the Traffic Control and to collaborate with related institutions. supporting the activities of the community traffic training. Keywords: Efforts, Traffic Education public, Traffic Accidents